Paramagnetic resonance in electron-impurity systems - Ivanchenko, E.A. (Вопросы атомной науки и техники, 2001)
The equation for the magnetization is obtained on the basis of the kinetic equation for an isotropic distribution function of electrons scattering on massive impurity centers in the presence of magnetic and electric fields. The analytical solution of the Cauchy problem for a given initial distribution of the magnetization under conditions of paramagnetic resonance is obtained. The estimated dynamic frequency shift of the forced precession has nonlocal and nonlinear dependence on the nonuniform distribution of the initial magnetization. The dynamic frequency shift of the free precession has only nonlocal character. Time and space dependence of the internal field is obtained. All results are expressed in terms of the initial distribution of the magnetization without specifying its functional form and in terms of the propagation function. These results may be used for analysis of spin diffusion in natural and manmade materials and also in magnetometry.